HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA DENGAN PERILAKU TIGA ANCAMAN DASAR KESEHATAN REPRODUKSI REMAJA(TRIAD KRR) PADA SISWA SMA NEGERI 1 MANCAK TAHUN 2023 - Sri Sukasmi; Abela Mayunita (Jurnal Ilmiah Global Education, 2023)
The aim of this research is to analyze the relationship between the level of knowledge and attitudes of adolescents with the behavior of the Three Basic Risk Threats to Adolescent Reproductive Health (TRIAD KRR) among students at SMA Negeri 1 Mancak in 2023. The research method used in this research is quasi experimental with purposive sampling with samples. 30 people. Data techniques include univariate analysis using frequency distributions and bivariate analysis using statistical calculations from the SPSS program. The results of this research show that there is a significant influence between knowledge and adolescent attitudes, with p value (0.000) < α (0.05) indicating that there is a significant relationship between knowledge and adolescent attitudes. Conclusions and Suggestions: There is a significant influence of knowledge on adolescent attitudes. It is hoped that teenagers will be aware of the behavior of the Three Basic Threats to Adolescent Reproductive Health (TRIAD KRR).